Rhizospheric Fungi to Plant Growth Promotion: A Review - Silva, João Manoel da; Montaldo, Yamina Coentro; Almeida, Arthur Costa Pereira Santiago de; Dalbon, Viviane Araújo; Acevedo, Juan Pablo Molina; Santos, Tania Marta Carvalho dos; Lima, Gaus Silvestre de Andrade (Journal of Agricultural Studies, 2021)
The rhizosphere is the region that has direct influence from the roots. This is the place where most of the interactions between microorganisms and plants occur. Studies involving the ecology of microbial communities from the rhizosphere became more frequent after the first reports of biological interactions of microorganisms with plants that influence physically and chemically modify the soil surrounding. According to these hypotheses, the rhizosphere mycobiota provides the development of plants through various mechanisms, direct and indirect. Thus, the objective of this review was to explain the aspects that provide characterizing these microorganisms as beneficial to plants in view of their applicability to agro-ecosystems. Therefore, it is stated that rhizospheric fungi have the solubilization of phosphorus (P), assimilating this nutrient for plants, promoting growth through the production or stimulation of the production of growth regulators such as 3-indole acetic acid, and control of phytopathogenic agents such as other filamentous fungi, and also phytonemamatodes. Therefore, it is possible to observe the importance of the constant observance of the action of these microorganisms in terms of their ecological role due to the agro-ecosystem.